Improving human nutrition through agriculture: the role of international agricultural research: conference summary and recommendations - Bouis, Howarth E. (United Nations University, 2000)
This paper reports the conference recommendations for priorities for future research and follow-up actions. It also summarizes the paper presentations and key points made by participants during the course of the conference. It includes partial transcripts of invited remarks made by several participants who were not asked to submit research papers. With respect to research, participants recommended continued efforts on breeding for nutritionally improved crop varieties, evaluation of the impact of the Consultative Group on International Agricultural Research (CGIAR) activities on nutritional outcomes, and new work on communication and outreach related to nutrition. Interdisciplinary research collaboration with non-CGIAR partners in these three broad areas was stressed. The need for a shift in emphasis from protein– energy malnutrition to micronutrient malnutrition was recognized. With respect to institutionally related follow-up actions, formation of an interdisciplinary task force was recommended to implement a process for development of a multidisciplinary common conceptual framework describing agriculture– nutrition linkages, which could then be used for evaluating integrated approaches to nutrition improvement; and to seek approval from the CGIAR Technical Advisory Committee for a system-wide initiative on human nutrition that would include partners from outside the CGIAR. Progress since the conference is reported.